Knockdown of Thitarodes host genes influences dimorphic transition of Ophiocordyceps sinensis in the host hemolymph - Sun, Tanqi; Jin, Yongling; Rao, Zhongchen; Liyan, Wang; Tang, Rui; Zaryab, Khalid Muhammad; Li, Mingyan; Li, Zhenhao; Wang, Ying; Xu, Jing; Han, Richou; Cao, Li (Frontiers in Cellular and Infection Microbiology, 2024)
The Chinese cordyceps, a unique parasitic complex of Thitarodes/Hepialus ghost moths and Ophiocordyceps sinensis fungus in the Tibetan Plateau, is a highly valuable biological resource for medicine and health foods in Asian countries. Efficient system for artificial cultivation of Chinese cordyceps relies on understanding the gene functions involved in the induction of growing blastospores into hyphae in the larval hemolymph of insect host, during O. sinensis infection. Transcriptome analysis and ribonucleic acid interference (RNA interference) method were employed to identify the key differentially expressed genes and to demonstrate their functions in Thitarodes xiaojinensis. Key larval genes critical for O. sinensis blastospore development or filamentation were identified. Nine of the 20 top upregulated genes encoded cuticles proteins, indicating that these proteins highly activated when the larval hemolymph was full of blastospores. Small interfering RNA (siRNA) knockdown of five larval genes such as Flightin, larval cuticle protein LCP-30, 26-hydroxylase (CYP18A1), cuticle protein 18.6, isoform B, and probable chitinase 3 significantly stimulated the dimorphic transition from blastospores to prehyphae in O. sinensis in the larval hemolymph after 120 h after injection. The expressions of these genes determined by quantitative real-time PCR were suppressed in various levels from 38.64% to 91.54%, compared to the controls. These results demonstrated that injection of the siRNAs of key upregulated genes into the larval hemolymph containing high load of blastospores caused the gene silence in T. xiaojinensis larvae and induced the fungal transition from blastospores to prehyphae, providing novel knowledge on the regulation of O. sinensis fungal dimorphism by Thitarodes host and cues for further study of Thitarodes biology and commercial cultivation of Chinese cordyceps.